Structure-guided development of heterodimer-selective GPCR ligands - Hübner, Harald; Schellhorn, Tamara; Gienger, Marie; Schaab, Carolin; Kaindl, Jonas; Leeb, Laurin; Clark, Timothy; Möller, Dorothee; Gmeiner, Peter (Nature Communications, 2016)
Crystal structures of G protein-coupled receptor (GPCR) ligand complexes allow a rational design of novel molecular probes and drugs. Here we report the structure-guided design, chemical synthesis and biological investigations of bivalent ligands for dopamine D-2 receptor/neurotensin NTS1 receptor (D2R/NTS1R) heterodimers. The compounds of types 1-3 consist of three different D2R pharmacophores bound to an affinity-generating lipophilic appendage, a polyethylene glycol-based linker and the NTS1R agonist NT(8-13). The bivalent ligands show binding affinity in the picomolar range for cells coexpressing both GPCRs and unprecedented selectivity (up to three orders of magnitude), compared with cells that only express D(2)Rs. A functional switch is observed for the bivalent ligands 3b,c inhibiting cAMP formation in cells singly expressing D(2)Rs but stimulating cAMP accumulation in D2R/NTS1R-coexpressing cells. Moreover, the newly synthesized bivalent ligands show a strong, predominantly NTS1R-mediated beta-arrestin-2 recruitment at the D2R/NTS1R-coexpressing cells.